2011
DOI: 10.1016/j.neuron.2011.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Integration in Hippocampal Dentate Granule Cells

Abstract: Hippocampal granule cells are important relay stations that transfer information from the entorhinal cortex into the hippocampus proper. This process is critically determined by the integrative properties of granule cell dendrites. However, their small diameter has so far hampered efforts to examine their properties directly. Using a combination of dual somatodendritic patch-clamp recordings and multiphoton glutamate uncaging, we now show that the integrative properties of granule cell dendrites differ substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
227
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(253 citation statements)
references
References 45 publications
23
227
0
2
Order By: Relevance
“…In their studies, V rest of DGCs remains at ϳϪ60 mV throughout all developmental stages, whereas E GABA shifts from ϳϪ40 to ϳϪ70 mV during development. In contrast, several other groups have found that DGCs have very negative V rest (from Ϫ80 to Ϫ85 mV) both in vitro (Staley and Mody, 1992;Schmidt-Hieber et al, 2004Alle and Geiger, 2006;Krueppel et al, 2011) and in vivo (Penttonen et al, 1997).…”
Section: Determining Gabaergic Actions Using a Noninvasive Approachmentioning
confidence: 70%
“…In their studies, V rest of DGCs remains at ϳϪ60 mV throughout all developmental stages, whereas E GABA shifts from ϳϪ40 to ϳϪ70 mV during development. In contrast, several other groups have found that DGCs have very negative V rest (from Ϫ80 to Ϫ85 mV) both in vitro (Staley and Mody, 1992;Schmidt-Hieber et al, 2004Alle and Geiger, 2006;Krueppel et al, 2011) and in vivo (Penttonen et al, 1997).…”
Section: Determining Gabaergic Actions Using a Noninvasive Approachmentioning
confidence: 70%
“…DG PCs receive excitatory inputs from the perforant path (PP) at their apical distal dendrites, electrotonically distant from the cell body. Thus, PP-mediated signals are strongly attenuated until they reach the soma (Krueppel et al, 2011). Furthermore, the voltage difference between the resting potential and spike threshold is large and has to be traversed to generate action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…To assess basal synaptic transmission in Pten cKO mice, we stimulated afferents in the medial perforant pathway and monitored the input/output relation of field excitatory postsynaptic potentials (fEPSPs) at synapses on DGCs. We focused on the DG because it is a critical checkpoint for the flow of information from the entorhinal cortex to the hippocampus (25) and exhibits progressive neuronal hypertrophy in Pten cKO mice by 14 wk of age (15). The input/output relation (fEPSP slope vs. stimulus intensity) at DGC synapses was unaltered in young (8-12 wk) and old (20-30 wk) Pten cKO mice, but enhanced in middle-aged (14-19 wk) Pten cKO mice relative to that of age-matched WT mice ( Fig.…”
Section: Basal Synaptic Transmission At Dgc Synapses Is Enhanced In Mmentioning
confidence: 99%